Risk factors of unmet needs among women with breast cancer in the post‐treatment phase. Issue 3 (16th December 2019) - Lo‐Fo‐Wong, Deborah N. N.; de Haes, Hanneke C. J. M.; Aaronson, Neil K.; van Abbema, Doris L.; den Boer, Mathilda D.; van Hezewijk, Marjan; Immink, Marcelle; Kaptein, Ad A.; Menke‐Pluijmers, Marian B. E.; Reyners, Anna K. L.; Russell, Nicola S.; Schriek, Manon; et al.
Abstract: Objective: Unmet health care needs require additional care resources to achieve optimal patient well‐being. In this nationwide study we examined associations between a number of risk factors and unmet needs after treatment among women with breast cancer, while taking into account their health care practices. We expected that more care use would be associated with lower levels of unmet needs. Methods: A multicenter, prospective, observational design was employed. Women with primary breast cancer completed questionnaires 6 and 15 months post‐diagnosis. Medical data were retrieved from medical records. Direct and indirect associations between sociodemographic and clinical risk factors, distress, care use, and unmet needs were investigated with structural equation modeling. Results: Seven hundred forty‐six participants completed both questionnaires (response rate 73.7%). The care services received were not negatively associated with the reported levels of unmet needs after treatment. Comorbidity was associated with higher physical and daily living needs. Higher age was associated with higher health system‐related and informational needs. Having had chemotherapy and a mastectomy were associated with higher sexuality needs and breast cancer‐specific issues, respectively. A higher level of distress was associated with higher levels of unmet need in all domains. Conclusions: Clinicians may use these results to timely identify which women are at risk of developing specific unmet needs after treatment. Evidence‐based, cost‐effective (online) interventions that target distress, the most influential risk factor, should be further implemented and disseminated among patients and clinicians.